Molecular classification of anaplastic oligodendroglioma using next-generation sequencing: a report of the prospective randomized EORTC Brain Tumor Group 26951 phase III trial - Dubbink, Hendrikus J. (Neuro Oncol, 2016)
BACKGROUND: Histopathological diagnosis of diffuse gliomas is subject to interobserver variation and correlates modestly with major prognostic and predictive molecular abnormalities. We investigated a series of patients with locally diagnosed anaplastic oligodendroglial tumors included in the EORTC phase III trial 26951 on procarbazine/lomustine/vincristine (PCV) chemotherapy to explore the diagnostic, prognostic, and predictive value of targeted next-generation sequencing (NGS) in diffuse glioma and to assess the prognostic impact of FUBP1 and CIC mutations. METHODS: Mostly formalin-fixed paraffin-embedded samples were tested with targeted NGS for mutations in ATRX, TP53, IDH1, IDH2, CIC, FUBP1, PI3KC, TERT, EGFR, H3F3A, BRAF, PTEN, and NOTCH and for copy number alterations of chromosomes 1p, 19q, 10q, and 7. TERT mutations were also assessed, with PCR. RESULTS: Material was available from 139 cases, in 6 of which results were uninformative. One hundred twenty-six tumors could be classified: 20 as type II (IDH mutation [mut], “astrocytoma”), 49 as type I (1p/19q codeletion, “oligodendroglioma”), 55 as type III (7+/10q– or TERTmut and 1p/19q intact, “glioblastoma”), and 2 as childhood glioblastoma (H3F3Amut), leaving 7 unclassified (total 91% classified). Molecular classification was of clear prognostic significance and correlated better with outcome than did classical histopathology. In 1p/19q codeleted tumors, outcome was not affected by CIC and FUBP1 mutations. MGMT promoter methylation remained the most predictive factor for survival benefit of PCV chemotherapy. CONCLUSION: Targeted NGS allows a clinically relevant classification of diffuse glioma into groups with very different outcomes. The diagnosis of diffuse glioma should be primarily based on a molecular classification, with the histopathological grade added to it. Future discussion should primarily aim at establishing the minimum requirements for molecular classification of diffuse glioma.